LIKUIDITAS SEBAGAI PEMODERASI PENGARUH UKURAN PERUSAHAAN PADA AUDIT REPORT LAG - Dewi, Ni Luh Nyoman Adi Kusuma; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 15 No 3 (2016), 2016)
The purpose of this study was to test the ability of liquidity in moderating the effect of firm size on audit report lag. This study uses data on manufacturing companies listed in Indonesia Stock Exchange 2012-2014. The samples in this study using purposive sampling method, with 63 companies and observational study of 189 samples obtained from www.idx.co.id. Data analysis technique used is multiple linear regression and moderation test using Moderated Regression Analysis (MRA). Results showed that the size of the company negatively affect audit report lag. This proves that the bigger the company the more short lagnya audit report. While liquidity is able to moderate the negative effects of company size on the audit report lag, which weakens the influence exerted negative influence on the company size audit report lag.
Keywords: Audit Report Lag, company size, liquidity